O processamento das atividades administrativas: o caso dos departamentos didáticos de uma universidade - Weber, Cláudia (2014)
The initiatives of innovations implemented in public organizations assume the search for efficiency and quality in services. To make these improvements happen effectively, Guimarães (2000) explains that it is necessary to break upwith the traditional models of managing resources and to introduce a new culture able to meet different requirements and complexities currently faced in this area. In the general context of the federal public administration, universities are bureaucratic agencies that require intensive studies on their organizational aspect, as well as a competent analysis of their administrative proceedings, since they are institutions with remarkable social responsibility because of their specific functions for generating and disseminating knowledge. This line of thinking corroborates the Institutional Development Plan (IDP) 2011-2015 of the Federal University of Santa Maria - UFSM, which shows the value of people, the quality of services, and the continuous improvement of working conditions as major challenges to be reached by the University. As a contribution to overcome these challenges, this study aimed to map the administrative proceedings within a Teaching Departments atCAL/UFSM and to identify difficulties to operationalize procedures. In order to achieve the objectives proposed, a study classified as a descriptive approach was carried out. In the research strategy, based on the Teaching Departments of Arts & Letters Center (CAL), the case study method was used to be aligned with the proposed objectives and with the research that guided the study. Data collection was conducted through document analysis and semi-structured interviews with the technical and administrative staff of the Teaching Departments at CAL. Results allowed us to learn about the quantitative of the administrative procedures regarding the department, as well as the classification of processes that require documentary formalization in Primers and Critics, based on the Valle e Oliveira (2009) model. Another significant element of the study was the identification of operational difficulties in implementing the procedures, since various demands have been pointed out. Moreover,operational and management practices rooted in the culture of the institution were demonstrated, which may boost debates aiming at institutional advantages. We have also designed a Tutorial,a practical tool aiming at operationalizing Critical processes, which may contribute to possible advances and positive effects ina department context. This research, with a view to the pursuit of excellence, may contribute to the consolidation of some changesas well as to the improvement of the management of people in order to stimulate more expressive, agile and consistent actions,which areexpected of a contemporary public organization.